Two-step synthesis of CdS (hcp) nanorods using sonochemical and hydrothermal processes - Phuruangrat A. (2014)
CdS (hcp) crystals were synthesized using CdCl 2.2H 2O in C 4H 11N containing 20% (NH 4) 2S by the 5 h sonochemical process followed by the hydrothermal reaction at different temperatures and times. CdS (hcp) crystals composing of Cd and S were detected using XRD, SAED and EDX. A Raman spectrometer revealed the presence of fundamental and overtone modes at 299 and 596 cm -1, respectively. The crystals are nanorods growing in systematic array analyzed using TEM and HRTEM. Their photoluminescence is in the blue spectral region at 409-422 nm (2.94-3.03 eV).